A march towards economic independence: An evaluation of the Filipino first policy of President Carlos P. Garcia, 1946-1961 - Guzman, Neanne Marie (Animo Repository, 2011)
The thesis is centered on the Filipino First Policy of President Carlos P. Garcia implemented from 1957 to 1961. It discusses how U.S. neocolonialism and its accompaniments became detrimental to Philippine economic development. In response, the post-war administrations, especially that of Garcia, espoused economic nationalism. As the conceptual framework of the study, economic nationalism is seen how President Garcia used this to cushion neocolonialism and give Filipinos a stand in their economy. Thus, study analyzes the post-war economic condition of the country leading to the Filipino First Policy. The policy is assessed with the explanation of its background, laws and measures. The study also discusses the impact of the policy on the country's economic development and realization of both political and economical freedom.